2009
DOI: 10.1021/jf803973y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chokeberry (Aronia melanocarpa) Juice on the Metabolic Activation and Detoxication of Carcinogenic N-Nitrosodiethylamine in Rat Liver

Abstract: Chokeberry is a rich source of polyphenols, which may counteract the action of chemical carcinogens. The aim of this study was to examine the effect of chokeberry juice alone or in combination with N-nitrosodiethylamine (NDEA) on phase I and phase II enzymes and DNA damage in rat liver. The forced feeding with chokeberry juice alone decreased the activities of enzymatic markers of cytochrome P450, CYP1A1 and 1A2. NDEA treatment also decreased the activity of CYP2E1 but enhanced the activity of CYP2B. Pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Nevertheless, chokeberry juice contains several classes of phenolic compounds which in combination might differently affect the lipase activity due to the different interaction between them as well as with other juice components. The results of qualitative and quantitative analyses of low molecular phenolic compounds by UPLC-MS and HPLC methods allowed to conclude that all most active juices had the same phenolic profile (Table 3), which was in accordance with the data published [9,34]. The major low molecular phenolic compounds of chokeberry juice were chlorogenic acids such as 3-and 5-O-caffeoylquinic acid.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, chokeberry juice contains several classes of phenolic compounds which in combination might differently affect the lipase activity due to the different interaction between them as well as with other juice components. The results of qualitative and quantitative analyses of low molecular phenolic compounds by UPLC-MS and HPLC methods allowed to conclude that all most active juices had the same phenolic profile (Table 3), which was in accordance with the data published [9,34]. The major low molecular phenolic compounds of chokeberry juice were chlorogenic acids such as 3-and 5-O-caffeoylquinic acid.…”
Section: Discussionsupporting
confidence: 87%
“…Results of in vitro and in vivo studies indicate that chokeberry juice has cardioprotective [7,8], hepatoprotective [9], and anti-diabetic effects [1] as well as anticancer activity [10]. Recent human studies also showed that Aronia melanocarpa juice may be useful in the treatment of obesity disorders [11].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effects of aronia fruits have been investigated in component analyses 9,10 . However, the effects of aronia on visceral fat accumulation, postprandial hyperlipidemia and hyperglycemia in rats with high-fat diet-induced obesity have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are considered to be critical environmental factors influencing cancer risk in humans, as they widely exist in the environment, in certain occupational settings, in food stuffs such as meat products and milk, as well as an endogenous formation in the human body from dietary components 3. A variety of studies have demonstrated that N-nitroso compounds could cause a wide range of tumors in many animal species 4-6. Nitrosodiethylamine (NDEA) is one of the most potent chemical hepatocarcinogens of this class, which can induce a variety of liver lesions in rodents.…”
Section: Introductionmentioning
confidence: 99%